2001
DOI: 10.1111/j.1945-5100.2001.tb01810.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate control on the thorium/uranium variations in ordinary chondrites: Improving solar system abundances

Abstract: Abstract-Isotope dilution thorium and uranium analyses by inductively-coupled plasma mass spectrometry of 12 samples of Harleton (L6) show a much larger scatter than was previously observed in equilibrated ordinary chondrites. Th/U linearly correlates with 1/U in Harleton and in the total equilibrated ordinary chondrite data set as well. Such a correlation suggests a two component mixture and this trend can be quantitatively modeled as reflecting variations in the mixing ratio between two phosphate phases: chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Chondrules and fractions of chondrule fragments have uranium concentrations of 9 -62 ppb, similar to or slightly higher than the values of ca. 10 ppb measured in whole rock samples of Richardton (Tilton, 1973;Tatsumoto et al, 1973;Abranches et al, 1980) and in other chondrites (Unruh, 1982;Göpel et al, 1994;Goreva and Burnett, 2001). Concentrations of U in the lowdensity fractions are similar.…”
Section: U-th-pb Systematicsmentioning
confidence: 73%
“…Chondrules and fractions of chondrule fragments have uranium concentrations of 9 -62 ppb, similar to or slightly higher than the values of ca. 10 ppb measured in whole rock samples of Richardton (Tilton, 1973;Tatsumoto et al, 1973;Abranches et al, 1980) and in other chondrites (Unruh, 1982;Göpel et al, 1994;Goreva and Burnett, 2001). Concentrations of U in the lowdensity fractions are similar.…”
Section: U-th-pb Systematicsmentioning
confidence: 73%
“…The measured activities of 232 Th eq are relatively uniform for all chondrites and correspond to an average of 50 ± 12 ppb Th (mean L chondrites: 40 ± 7 ppb, Th/U = 3.53; Goreva and Burnett ). Good agreement is seen between the values from the different transitions, before and after 220 Rn in the decay chain.…”
Section: Resultsmentioning
confidence: 90%
“…While both merrillite and apatite are present, U concentrations in apatite are as much as 159 higher (Crozaz et al 1989). Furthermore, Goreva and Burnett (2001) have shown that the relatively high P/Cl ratios in OCs, as well as heterogeneously distributed Cl, results in homogeneous distribution of merrillite and very heterogeneous distribution of chlorapatite. The low U value in MG suggests that mg-sized sampling is too small to obtain reliable results for this element.…”
Section: Bulk Chemistrymentioning
confidence: 99%